2021
DOI: 10.1039/d1ra03621a
|View full text |Cite
|
Sign up to set email alerts
|

A GGA + U investigation into the effects of cations on the electromagnetic properties of transition metal spinels

Abstract: Jahn–Teller active ions Fe2+, Ni2+, Mn3+, Ni3+, Cr4+ and Fe4+ can effectually regulate the electronic structures of transition metal spinels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
2
4
0
Order By: Relevance
“…It is noted that the orbital occupancies and magnetic moments calculated by the DFT+ U approach used in our study will depend on the value of U used. 57 Nevertheless, our results are consistent with experimental reports of the presence of Fe 2+ and Mn 3+ in members of this solid solution.…”
Section: Solid Solution Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…It is noted that the orbital occupancies and magnetic moments calculated by the DFT+ U approach used in our study will depend on the value of U used. 57 Nevertheless, our results are consistent with experimental reports of the presence of Fe 2+ and Mn 3+ in members of this solid solution.…”
Section: Solid Solution Propertiessupporting
confidence: 92%
“…It is noted that the orbital occupancies and magnetic moments calculated by the DFT+U approach used in our study will depend on the value of U used. 57 Nevertheless, our results are consistent with experimental reports of the presence of Fe 2+ and Mn 3+ in members of this solid solution. This section highlights the physical properties that can be obtained across an entire spinel phase space using the new vc-ChemDASH methodology.…”
Section: Pccp Papersupporting
confidence: 92%
“…Figure S9, Supporting Information). [ 112–114 ] For the HEF and MEF, valence band maxima of ‐6.35 eV and ‐4.51 eV were obtained, respectively. The DFT derived VBM agree with the Mott–Schottky data and confirm that the HEFs are in principle capable of performing unassisted water oxidation, while the MEF are not, due to positioning of the VBM above the oxidation potential of water (see Figure 6 and Figure S9, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Gamma-point-centered (5 × 5 × 3) k-meshes were used for the super cell calculations. To account for the local electron correlation at the transition metal cation sites, a Hubbard-correction of 4.5 eV, [112] 4 eV, [112] and 5 eV, [113,114] was applied to Fe, Co, Ni, and Cu, respectively. The DOS and absolute band alignment of unrelaxed cells in ferromagnetic state were computed by correcting the band energies by the averaged bulk potential versus the vacuum potential.…”
Section: Methodsmentioning
confidence: 99%
“…Analogously, Fe 3+ (t 2g 3 e g 2 ) with a high-spin state induces the transition of Co 3+ in the O h sites from a low-spin to an intermediate spin state. These electronic configurations of the 3d orbital of transition metals have been intensively clarified in recent years using DFT calculations. , Consequently, Ni or Fe addition enhances the OER activity by stabilizing surface intermediates (e.g., M–OH, M–O*, and M–OOH) during the rate-limiting step (step 3) at the O h sites, presumed to be related to the changes in the oxidation state and the local structural distortion of the active species. Furthermore, by replacing Co 2+ with Zn 2+ ions in T d sites to form the ZnCo 2 O 4 catalyst, some systematic investigations were performed to reveal the individual roles of Co 2+ ions and Co 3+ ions during the OER. The invariable oxidation state and coordination preference of Zn 2+ in the T d sites implies that the Co ions in the O h sites play a major role in the OER by comparing the OER performance of Co 3 O 4 and ZnCo 2 O 4 . , On the contrary, a previous in situ XAFS study , reported that Co 2+ and Co 3+ ions play different roles in OER activity and the Co 2+ ions in the T d sites dominated the OER activity.…”
Section: Resultsmentioning
confidence: 99%